The Causality Between Industrial Development and Economic Growth: A Case of Pakistan - Qayyum, Aaqib; Khalid, Nayab; Muhammad Usman (Daengku: Journal of Humanities and Social Sciences Innovation, 2021)
Industrial sector is the paramount factor in the development of economic growth. This study has analysed the industrial pantomime in case of Pakistan. Times series data has been used for 40 years, from 1980-2020. Initially the data has been checked for stationarity, by applying ADF, test which proved that, all the indicators are stationary at level. This confirms that, we are allowed to apply OLS regression analysis for the desired results. The study concluded that there has been positive and significant relationship between industrial construction and economy activity of Pakistan. Only factor that, induces negative impact on the economic growth, is the excessive consumption of energy resources; growth of electricity, gas and water supply. Foreign direct investment indicated negative association with the economy, but also gives the insignificant results.